2014
DOI: 10.3390/ijms15046169
|View full text |Cite
|
Sign up to set email alerts
|

Differential Signaling by Protease-Activated Receptors: Implications for Therapeutic Targeting

Abstract: Protease-activated receptors (PARs) are a family of four G protein-coupled receptors that exhibit increasingly appreciated differences in signaling and regulation both within and between the receptor class. By nature of their proteolytic self-activation mechanism, PARs have unique processes of receptor activation, “ligand” binding, and desensitization/resensitization. These distinctive aspects have presented both challenges and opportunities in the targeting of PARs for therapeutic benefit—the most notable exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 79 publications
0
35
0
1
Order By: Relevance
“…We also showed that LPS failed to induce lung injury in PAR1-null mice. PAR1 and PAR2 are known to play opposing roles in thrombin-induced signaling in several cell types (Kahn et al, 1999; Sidhu et al, 2014; Soh et al, 2010). We therefore speculate from these findings that thrombin-mediated activation of PAR1 in AM-induced Ca 2+ entry through the plasmalemmal channel.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that LPS failed to induce lung injury in PAR1-null mice. PAR1 and PAR2 are known to play opposing roles in thrombin-induced signaling in several cell types (Kahn et al, 1999; Sidhu et al, 2014; Soh et al, 2010). We therefore speculate from these findings that thrombin-mediated activation of PAR1 in AM-induced Ca 2+ entry through the plasmalemmal channel.…”
Section: Discussionmentioning
confidence: 99%
“…Because alterations in early outside‐in signaling (such as phosphorylation of c‐Src) are characteristic of thrombin receptor‐promoted integrin outside‐in signaling , the regulation pattern of Shp2 (only influencing late outside‐in signaling) further dissociates Shp2 from the pathways mediated by thrombin receptors. Thus, Shp2 may serve as a signal to distinguish the pathway initiated by TP from that initiated by protease‐activated receptor 4, although both GPCRs share common downstream G‐proteins (Gα q and Gα 12/13 ) to regulate platelet activation .…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Accordingly, these signaling pathways are essential in the maintenance of vascular homeostasis. [8][9][10][11] Recent advances in the cardiovascular characterization of PAR signaling make them extremely attractive for drug targeting 3 ; however, how PARs regulate the human eNOS/ NO pathway remains unclear. Studies have shown that multiple PARs modulate the production of NO via posttranslational modifications of endothelial nitric oxide synthases (eNOS) via specific phosphorylation of various regulatory sites.…”
Section: Introductionmentioning
confidence: 99%